Reinforced brick design in accordance to BS 5628 / Kaharuddin Mohamed Ali - Mohamed Ali, Kaharuddin (1994)
The work presented in this thesis is focused on the design in reinforced brick. Although brick have popularly been used in construction, the usage are just a mere cladding or housing materials and not as high structural potential. Brickwork just like concrete can be reinforced to carry the tensile stresses to eliminate the weakness in tension. The structural components that involved in this thesis are beam, wall, ie. quetta bond wall and grouted cavity wall and column. Computer program was written using C language, to facilitate the user in obtaining the result in a short duration of time. The outline of the design are based on BS 5628 and W.G. Curtin et al. The analysis of beam was subjected to pure bending members where the section of the beam and the required reinforcement bar are simulated from the characteristics loading given. Quetta bond wall design analysis is based solely on axially loaded members and the design will provide the size of reinforcement bar to suit into the standard quetta bond vertical grouted duct. Grouted cavity wall is a double leaf wall separated with a grouted cavity layer that embedded the steel reinforcement bar. The analysis involved are based on:-